Titanium alloy cold-drawn seamless super-long tube and method for manufacturing the same
Patent Information
- Application Number
- CN202611019145.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-30
AI Technical Summary
[0013]现有钛合金冷轧管为主要涉及的牌号为TA15、TA17、TA18CF、TA23、TA24、TC3、TC4、TC4ELI、Ti32或TC16;主要的加工工艺为:精锻(热挤压)-斜轧穿孔-热轧-多道次往复冷轧,工艺方案仅解决了冷轧管材成型的问题,无法实现≥1000m超长钛合金管材的制备
(1)本发明限定钛合金的组成,能完全适应高含H2S、CO2环境,完全解决钛合金材质焊接难度大、焊接效果不佳的问题,管体本身不含焊缝、热影响区,避免了焊缝、热影响区组织不均导致的管材容易腐蚀、失效等问题;
Smart Images

Figure CN122999733A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of seamless titanium alloy tube materials, and more particularly to a cold-drawn seamless ultra-long titanium alloy tube and its preparation method. Background Technology
[0002] With the increasing demand for oil and gas resources, oil and gas field development is gradually moving towards greater depths, resulting in the emergence of ultra-deep wells with high temperatures and pressures. These wells typically contain CO2, H2S, and Cl. - High temperature, high pressure, and high chloride ion corrosion conditions at the bottom of wells limit the application of martensitic stainless steel, duplex stainless steel, and nickel-based alloy tubing. Titanium alloy tubing has high specific strength, good high-temperature mechanical properties, and extremely strong corrosion resistance. Since the mid-1980s, it has been used in some high-temperature, high-pressure, and ultra-high-temperature, high-pressure hot acidic oil and gas wells (such as the Gulf of Mexico). With the increasing development of (ultra) high H2S / CO2 oil and gas fields, the demand for titanium alloy tubing is increasing.
[0003] In oil and gas exploration and development, downhole control tubing (also known as control lines or capillary lines) is the "lifeline" connecting the surface control system to tools such as downhole safety valves and chemical injection valves. With the development of deep wells, ultra-deep wells, and high-sulfur gas fields, the downhole environment faces high temperatures (above 150°C), high pressures (above 70 MPa), and high concentrations of H2S, CO2, and Cl-. - The intense corrosion challenges present significant challenges. Traditional carbon steel and low-alloy steel control pipes are prone to sulfide stress corrosion cracking (SSC) and hydrogen-induced corrosion cracking (HIC) in these environments, resulting in short service life and substantial safety hazards. While nickel-based alloy pipes exhibit excellent corrosion resistance, their extremely high cost and density increase the weight of the tubing string. Titanium alloys, due to their high specific strength and excellent corrosion resistance (exhibiting near-perfect corrosion resistance in almost all oil and gas field environments), have become an ideal alternative material.
[0004] In existing technologies, titanium alloy pipes are manufactured using welding processes. During welding, these alloys readily react with elements such as hydrogen, oxygen, and nitrogen. Titanium alloys can rapidly absorb hydrogen above 300°C, oxygen above 450°C, and nitrogen above 600°C, making welding difficult and resulting in weak welded areas. When these harmful gases intrude into the molten pool, the plasticity and toughness of the weld joint change significantly, especially above 882°C. The joint grains become severely coarsened, forming martensitic structures upon cooling. This leads to a decrease in the joint's strength, hardness, plasticity, and toughness, a severe tendency to overheat, and severe embrittlement.
[0005] Publication No. CN 121137404A discloses a high corrosion-resistant titanium alloy coiled tubing and its preparation method, which is a titanium alloy ultra-long tubing resistant to high temperature and high pressure corrosion and its preparation method. The main alloying elements involved include: Al: 0.6~1.7%; Mo: 0.4~1.9%; Ni: 0.7~1.8%; Nb: 0.5~1.5%; Ru: 0.02~0.08%; O: 0.08~0.2%; Fe≤0.05%. The manufacturing method is conventional slitting of rolled plates, butt welding of steel strips, and welding of the entire tubing.
[0006] Publication No. CN 114523271B discloses the preparation methods and applications of various pure titanium grades TA0, TA1, TA2, TA3, TA4, TA5, TA6, TA7, TA8, TA8-1, TA9, TA9-1, TA10, TA11, TA15, TA17, TA18, TC1, TC2, TC3, TC4 and TC4ELI ultra-long tubing. The manufacturing methods are conventional methods of slitting rolled plates, butt welding of steel strips, and welding of the entire tubing.
[0007] Publication No. CN 104404299B discloses an ultra-long tube made of titanium alloy continuous tubing and its manufacturing method. The tube has the following chemical composition: Al: 2~5.5; 4V: 1.5~3; Ni: 0.6~O0.9; Mo: 0.2~0.4; Fe: ≤0.30; C: ≤0.08; N: ≤0.05; O: ≤0.025; H: ≤0.1; with the balance being titanium. The manufacturing method is a conventional method of rolling plate longitudinal shearing, steel strip butt welding, and integral tube welding.
[0008] Publication No. CN 120696223A discloses a method for preparing high-strength TC16 titanium alloy cold-rolled tubes with a wall thickness of 1.0mm~2.0mm. The method involves obtaining TC16 titanium alloy cold-rolled tubes by ingot rolling followed by skew rolling and piercing, and then multiple cold rolling passes.
[0009] Publication No. CN 110983105A discloses a high-strength titanium alloy suitable for cold rolling and its preparation method. The composition is as follows: Al 3%~4.5%, Mo 2.5%~3.5%, Cr 1.5%~2.5%, Fe 1.5%~2.0%, with the balance being Ti. The main manufacturing process involved is skew rolling piercing-heat treatment-cold rolling-annealing.
[0010] Publication No. CN 114700387B discloses a method for preparing high-strength titanium alloy cold-rolled tubes; the main production process is precision forging (hot extrusion) - skew rolling piercing - hot extrusion / hot rolling - cold rolling - surface treatment, and the materials include TA15, TA17, TA18CF, TA23, TA24, TC3, TC4, TC4ELI, Ti32 or TC16.
[0011] Publication No. CN 117564728A discloses a method for preparing TA15 titanium alloy cold-rolled tubes, which involves processing TA15 titanium alloy ingots into bar billets; obtaining hollow bar billets by drilling and boring; hot extrusion, straightening, and pickling of the hollow bar billets to obtain extruded tube blanks; and rolling the extruded tube blanks in multiple passes to obtain rolled tubes.
[0012] Publication No. CN 120055073A discloses a manufacturing method for TA24 titanium alloy cold-rolled tubes for ships; the manufacturing method mainly includes: ingot forging - hot extrusion - whole tube rolling - inner and outer surface treatment - heat treatment - cold rolling - heat treatment - inner surface sandblasting - pickling - straightening and ultrasonic flaw detection.
[0013] The existing titanium alloy cold-rolled tubes mainly involve grades TA15, TA17, TA18CF, TA23, TA24, TC3, TC4, TC4ELI, Ti32, or TC16; the main processing technology is: precision forging (hot extrusion) - skew rolling piercing - hot rolling - multi-pass reciprocating cold rolling. The process solution only solves the problem of cold-rolled tube forming and cannot realize the preparation of ultra-long titanium alloy tubes ≥1000m. Summary of the Invention
[0014] The purpose of this invention is to provide a cold-drawn seamless ultra-long titanium alloy tube and its preparation method. The preparation method provided by this invention can produce cold-drawn seamless ultra-long titanium alloy tubes with a length ≥100m and high strength and high corrosion resistance.
[0015] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a cold-drawn seamless ultra-long titanium alloy tube, comprising: Titanium alloy is sequentially smelted, forged, hot extruded, skew rolling pierced, multi-pass cold rolling and multi-pass cold drawing to obtain a seamless ultra-long titanium alloy tube. The titanium alloy, by mass percentage, comprises: aluminum 0~6.0%, vanadium 0~4.5%, tin 0~3.0%, palladium 0.12~0.25%, iron 0~0.3%, carbon 0~0.08%, hydrogen 0~0.015%, oxygen 0~0.15%, nitrogen 0~0.05%, and the balance Ti; The multi-pass cold rolling includes roughing and finishing; the ratio of diameter reduction to wall reduction in each pass of cold rolling is independently 0.53 to 1.40.
[0016] Beneficial effects: (1) The present invention limits the composition of titanium alloy, which can fully adapt to the environment with high H2S and CO2 content, and completely solves the problems of high welding difficulty and poor welding effect of titanium alloy material. The pipe body itself does not contain weld seam or heat-affected zone, thus avoiding problems such as easy corrosion and failure of pipe material caused by uneven structure of weld seam and heat-affected zone. (2) The present invention uses a forging process to process titanium alloy ingots, and obtains hot extruded billets by continuous drawing; (3) The present invention creatively uses hot extrusion to fully crush the ingot, and obtains hot extruded bars with extremely fine grain size; (4) The preparation of ultra-long titanium alloy cold-rolled tube blanks was achieved by skew rolling piercing; (5) The present invention adopts multi-pass cold rolling, which greatly improves the production efficiency of titanium alloy tubes; (6) The present invention adopts multi-pass cold drawing to improve the surface precision of titanium alloy tubes and further enhances the corrosion resistance of titanium alloy surface; (7) The titanium alloy cold-drawn seamless ultra-long tube of the present invention has a yield strength ≥755MPa, tensile strength ≥860MPa, elongation after fracture ≥10%, tube diameter Φ3.0~Φ50.8mm, single length ≥100m, and has high strength. Attached Figure Description
[0017] Figure 1 This is a flowchart illustrating the preparation process of the cold-drawn seamless ultra-long titanium alloy tube of the present invention. Figure 2 This is a metallographic diagram of the cold-drawn seamless ultra-long titanium alloy tube in Embodiment 1 of the present invention. Detailed Implementation
[0018] This invention provides a method for preparing a cold-drawn seamless ultra-long titanium alloy tube, comprising: Titanium alloy is subjected to melting, forging, hot extrusion, skew rolling piercing, multi-pass cold rolling and multi-pass cold drawing to obtain a seamless ultra-long titanium alloy tube.
[0019] In this invention, the titanium alloy, by mass percentage, comprises: aluminum 0~6.0%, vanadium 0~4.5%, tin 0~3.0%, palladium 0.12~0.25%, iron 0~0.3%, carbon 0~0.08%, hydrogen 0~0.015%, oxygen 0~0.15%, nitrogen 0~0.05%, and the balance Ti.
[0020] The titanium alloy of the present invention comprises 0-6.0% aluminum by weight, preferably 2.0-3.5%. As one embodiment, the aluminum content may specifically be 2.0%, 2.5%, 3.0%, or 3.5%. Limiting the aluminum content in the titanium alloy to the above range ensures that the titanium alloy has good corrosion resistance.
[0021] The titanium alloy of the present invention comprises 0-4.5% vanadium by mass percentage, preferably 1.5-3.0%. As one embodiment, the vanadium content may specifically be 1.5%, 2.0%, 2.5%, or 3.0%. Limiting the vanadium content in the titanium alloy to the above range ensures that the titanium alloy has good corrosion resistance.
[0022] The titanium alloy of this invention comprises 0-3.0% tin by weight, preferably 2.0-3.0%. As one embodiment, the tin may specifically be 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, or 3.0%. Limiting the vanadium content in the titanium alloy to the above range ensures that the titanium alloy has good corrosion resistance.
[0023] The titanium alloy of the present invention comprises 0-0.25% palladium by mass percentage, preferably 0.12-0.25%. As one embodiment, the palladium content can specifically be 0.12%, 0.14%, 0.16%, 0.18%, 0.20%, 0.22%, 0.24%, or 0.25%. Limiting the palladium content in the titanium alloy to the above range ensures that the titanium alloy has good corrosion resistance.
[0024] The titanium alloy of the present invention comprises 0-0.3% iron by mass percentage, preferably 0.01-0.3%. As one embodiment, the iron content may specifically be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, or 0.3%. Limiting the iron content in the titanium alloy to the above range ensures that the titanium alloy has good corrosion resistance.
[0025] The titanium alloy of this invention comprises 0 to 0.08% carbon by weight percentage. As one embodiment, the carbon content may specifically be 0.05%, 0.07%, 0.07%, or 0.08%. Limiting the carbon content in the titanium alloy to the above range ensures that the titanium alloy exhibits good corrosion resistance.
[0026] The titanium alloy of the present invention comprises 0-0.015% hydrogen by mass percentage, preferably 0.001-0.015%. As one embodiment, the hydrogen content may specifically be 0.001%, 0.005%, 0.01%, or 0.015%. Limiting the hydrogen content in the titanium alloy to the above range ensures that the titanium alloy has good corrosion resistance.
[0027] The titanium alloy of this invention comprises 0-0.15% oxygen by mass percentage, preferably 0.01-0.1%. As one embodiment, the oxygen content can specifically be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, or 0.1%. Limiting the oxygen content in the titanium alloy to the above range ensures that the titanium alloy exhibits good corrosion resistance.
[0028] The titanium alloy of this invention comprises 0-0.05% nitrogen by mass percentage. As one embodiment, the nitrogen may specifically be 0.01%, 0.02%, 0.03%, 0.04%, or 0.05%. Limiting the nitrogen content in the titanium alloy to the above range ensures that the titanium alloy has good corrosion resistance.
[0029] In one embodiment of the present invention, the smelting method can be vacuum arc remelting (VAR) or cold hearth furnace smelting. The present invention utilizes these smelting methods to better smelt metallic titanium.
[0030] This invention does not impose a specific limitation on the melting temperature; those skilled in the art can select the temperature conventionally based on the composition of the titanium alloy. In embodiments of this invention, the melting temperature is 1660~1668℃.
[0031] In one embodiment of the present invention, after the smelting is completed, casting and a first post-processing can be performed to obtain an ingot. The present invention does not impose any special limitations on the casting operation; casting operations commonly used by those skilled in the art can be employed.
[0032] In one embodiment of the present invention, after the casting is completed, the cast product is subjected to a first post-processing to obtain an ingot.
[0033] As one embodiment of the present invention, the first post-processing includes sequentially performing flaw detection, a first descaling process, and a first flaw detection and grinding.
[0034] In one embodiment of the present invention, the flaw detection specifically involves using low-frequency ultrasonic flaw detection according to the testing method of GB / T 5193-2020 to control the density and purity of the casting product's microstructure, ensuring that the casting product is free of high-density inclusions (tungsten and molybdenum fragments) and low-density inclusions (oxides and nitrides), thus meeting the GB / T 5193-2020 standard. In this invention, casting products that fail the flaw detection need to be remelted, and casting products whose performance meets the GB / T 5193-2020 standard are used for subsequent operations.
[0035] In one embodiment of the present invention, the oxide scale removed by the first descaling process can be 3-5 mm thick; the equipment used for the first descaling process can be a heavy-duty lathe.
[0036] As one embodiment of the present invention, the first flaw detection and grinding can specifically be as follows: manually using heavy machine oil to perform defect detection on the product after the first descaling treatment, using a 5MHz or 2.5MHz small crystal straight probe to check for small defects in the near-surface area (0~100mm), using a 2.25MHz straight probe to check for small defects in the middle area (100mm~400mm), using a 1.0MHz high-power straight probe to check for larger defects in the core (>400mm), and using a grinding wheel to grind the flaw detection defect location to remove the flaw detection defect. The flaw detection and grinding test results need to meet the standard of GB / T 5193-2020.
[0037] In one embodiment of the present invention, after obtaining the ingot, the ingot can be forged to obtain a forged billet.
[0038] In one embodiment of the present invention, the ingot can be homogenized before forging; the temperature of the homogenization treatment can be 950~1200℃; the time of the homogenization treatment can be ≥15h, or 15~50h. By limiting the temperature and time of the homogenization treatment to the above ranges, the present invention can better homogenize the ingot.
[0039] As one embodiment of the present invention, the forging may include β phase region billet drawing, α+β phase region reforging and finishing.
[0040] In one embodiment of the present invention, the cross-sectional change rate of the β-phase region during blanking and elongation can be 50-70%, or even 55-65%; the cross-sectional change rate of the α+β phase region during reforging can be 40-55%, or even 45-50%; and the cross-sectional change rate of the finishing process can be 10-20%, or even 12-18%. By limiting the forging deformation to the above ranges, the present invention can improve the uniformity of the microstructure within the forged billet and increase the strength of the final product.
[0041] The forging process described in this invention is as follows: after homogenization treatment, the ingot is sequentially subjected to β phase region forging at 1000~1050℃, α+β phase region reforging at 880~920℃, and finishing at 850~880℃.
[0042] As one embodiment of the present invention, after the forging is completed, the forging product can be subjected to a second post-processing to obtain a forging billet.
[0043] In one embodiment of the present invention, the second post-processing includes a second descaling process and a second flaw detection and grinding process performed sequentially.
[0044] In one embodiment of the present invention, the second descaling treatment may specifically involve: sequentially subjecting the forging billet to sandblasting or alkaline washing, pickling, water washing, and mechanical grinding; the pickling solution used for pickling may be 1-5% (v / v) hydrofluoric acid or 15-40% (v / v) nitric acid; the water used for water washing may be hot water. The present invention does not specifically limit the sandblasting operation or the concentration of the alkaline washing solution used; any sandblasting operation or alkaline washing solution concentration commonly used by those skilled in the art can be adopted. The present invention does not specifically limit the mechanical grinding operation; any oxide scale not removed after pickling can be removed using any mechanical grinding operation commonly used by those skilled in the art.
[0045] As one embodiment of the present invention, the second flaw detection and grinding operation can be specifically as follows: manually using heavy machine oil to perform defect detection on the descaling forged billet, using a 5MHz or 2.5MHz small crystal straight probe to check for minor defects in the near-surface area (0~100mm), using a 2.25MHz straight probe to check for minor defects in the middle area (100~400mm), grinding the flaw detection defect location with a grinding wheel to remove the flaw detection defect, and the flaw detection and grinding test results need to meet the standard of "GB / T 5193-2020".
[0046] In one embodiment of the present invention, after obtaining the forging blank, the forging blank can be hot-extruded to obtain a hot-extruded blank.
[0047] In one embodiment of the present invention, the hot extrusion can be a multi-pass hot extrusion; the number of passes in the multi-pass hot extrusion can be 1 to 3; the temperature of each pass in the multi-pass hot extrusion can be independently 850 to 1000°C; the process of heating to the hot extrusion temperature can be: first heating the forging billet to 640 to 660°C and holding it for 1 to 2 hours, then heating it to 850 to 1000°C and holding it for 4 to 5 hours; the cross-sectional change rate of each pass in the hot extrusion can be independently 66.7 to 90%, or independently 70 to 80%; the extrusion ratio of each pass in the hot extrusion can be independently 3 to 10, or independently 3 to 8, or independently 4 to 7. By limiting the number of passes, extrusion temperature, and extrusion ratio of the hot extrusion to the above ranges, the present invention can extrude large-sized titanium alloy bars, laying a good foundation for subsequent skew rolling piercing, obtaining long bars with uniform microstructure, and providing conditions for skew rolling piercing of ultra-long tubes.
[0048] As one embodiment of the present invention, after the hot extrusion is completed, the hot extrusion product can be subjected to a third post-processing to obtain a hot extrusion billet.
[0049] As one embodiment of the present invention, the third post-processing may include a third descaling process and a third flaw detection and grinding process.
[0050] In one embodiment of the present invention, the third descaling process can specifically be as follows: immersing the hot-extruded billet in an acid solution for pickling, followed by water washing to remove the oxide scale; the acid solution is a mixture of HF, HNO3, and water; the volume concentration of HF in the acid solution is 3-5%; the volume concentration of HNO3 in the acid solution is 20-35%; and the water used for washing is hot water (≤60℃). The use of hot water for washing in this invention can accelerate drying.
[0051] In one embodiment of the present invention, the third descaling treatment can be followed by drying. The present invention does not specifically limit the drying operation and parameters; commonly used drying operations and parameters by those skilled in the art can be employed to dry the moisture on the surface of the hot-extruded tube blank after the third descaling treatment.
[0052] As one embodiment of the present invention, the third flaw detection and grinding operation can specifically be as follows: ultrasonic and eddy current flaw detection of cold-rolled tube blanks are performed online using the ultrasonic flaw detection method of titanium and titanium alloy tubes in GB / T12969.1 and the eddy current detection method of titanium and titanium alloys in GB / T 12969.2. If the flaw detection results meet the standard requirements, the defect location is ground to eliminate the defect.
[0053] In this invention, after obtaining the hot-extruded billet, the hot-extruded billet is subjected to skew rolling and piercing to obtain a thick-walled tube.
[0054] In one embodiment of the present invention, the hot extrusion billet can be heated before skew rolling and piercing; the heating can be carried out in a homogenizing furnace; the heating can specifically be: first heating the forging billet to 640~660℃ and holding it for 1~2 hours, then raising the temperature to 820~900℃ and holding it for 4~5 hours.
[0055] In one embodiment of the present invention, the skew rolling piercing can be performed in a skew rolling piercing mill; the total cross-sectional change rate during the skew rolling piercing can be 30-70%.
[0056] As one embodiment of the present invention, after the skew rolling piercing is completed, the skew rolling piercing product can be subjected to a fourth post-processing to obtain a thick-walled tube.
[0057] In one embodiment of the present invention, the fourth post-processing includes a fourth descaling process and a fourth flaw detection and grinding process performed sequentially.
[0058] In one embodiment of the present invention, the fourth descaling process can specifically be as follows: immersing the thick-walled capillary tube in an acid solution for acid washing followed by water washing to remove the oxide scale; the acid solution is a mixture of HF, HNO3, and water; the volume concentration of HF in the acid solution is 3-5%; the volume concentration of HNO3 in the acid solution is 20-35%; and the water used for washing is hot water (≤60℃). The use of hot water for washing in this invention can accelerate drying.
[0059] In one embodiment of the present invention, the fourth descaling treatment can be followed by drying. The present invention does not specifically limit the drying operation and parameters; commonly used drying operations and parameters by those skilled in the art can be employed to dry the moisture on the surface of the thick-walled capillaries after the fourth descaling treatment.
[0060] As one embodiment of the present invention, the fourth flaw detection and grinding operation can be specifically as follows: ultrasonic and eddy current flaw detection are performed online on the thick-walled capillary tube that has undergone the fourth descaling treatment using the ultrasonic flaw detection method for titanium and titanium alloy tubes in GB / T12969.1 and the eddy current testing method for titanium and titanium alloy tubes in GB / T 12969.2. If the flaw detection results meet the standard requirements, the defect location is ground to eliminate the defect.
[0061] In one embodiment of the present invention, after obtaining the thick-walled tube, the thick-walled tube can be subjected to multiple cold rolling passes to obtain a cold-rolled tube blank.
[0062] In this invention, the multi-pass cold rolling includes roughing and finishing rolling.
[0063] In one embodiment of the present invention, the ratio of the reduction rate to the wall reduction rate in each roughing pass can be 0.53~1.40, 0.60~1.30, 0.70~1.20, or 0.80~1.10. Limiting the ratio of the reduction rate to the wall reduction rate in each roughing pass to the above range ensures uniform deformation and prevents internal surface cracks.
[0064] In one embodiment of the present invention, the number of passes of rough rolling can be 2 to 4, or 2 to 3; the reduction rate of cross-sectional area of each pass of rough rolling can be independently 20 to 45%, or 25 to 40%.
[0065] As one embodiment of the present invention, when the cumulative cross-sectional area reduction rate during the rough rolling stage reaches 50-70%, an intermediate annealing treatment is performed to eliminate work hardening; the intermediate annealing treatment temperature is 700-800℃, the holding time is 1-2h, and then air cooling is performed.
[0066] As one embodiment of the present invention, the total cross-sectional area reduction rate of the finishing rolling can be 15-45%, or 25-40%; the cross-sectional area reduction rate of each finishing rolling pass can be independently 10-35%, or 15-35%.
[0067] The present invention limits the parameters of roughing and finishing in cold rolling to the above range, which can better break down the grains and provide more and more uniform nucleation sites for subsequent annealing.
[0068] In the cold rolling process described in this invention, the selection of the mandrel can be made according to the tube specifications, deformation stage, and requirements for internal surface quality and dimensional accuracy. This invention selects a fixed short mandrel in the thick-walled tube or billet stage to ensure thorough and stable deformation; and selects a floating mandrel in the thin-walled tube, finished product pass, or long tube production to obtain better surface quality, higher precision, and efficiency.
[0069] As one embodiment of the present invention, after the multi-pass cold rolling is completed, the multi-pass cold-rolled product can be subjected to a fifth post-processing to obtain a cold-rolled tube blank.
[0070] In one embodiment of the present invention, the fifth post-processing is a fifth flaw detection and grinding process.
[0071] In this invention, the fifth flaw detection and grinding operation can specifically be as follows: ultrasonic and eddy current testing are performed on the cold-rolled tube blank online using the ultrasonic flaw detection method of titanium and titanium alloy tubes in GB / T 12969.1 and the eddy current testing method of titanium and titanium alloys in GB / T 12969.2. The flaw detection results meet the requirements of the GB / T 3625 standard. The defect location is then ground to remove the oxide scale from the defect area.
[0072] After obtaining the cold-rolled tube blank, the present invention performs multiple cold drawing processes on the cold-rolled tube blank to obtain a titanium alloy cold-drawn seamless ultra-long tube.
[0073] In one embodiment of the present invention, the surface of the cold-rolled tube blank can be immersed in cold-drawing lubricant before the multi-pass cold drawing, and then the cold drawing can be performed.
[0074] In one embodiment of the present invention, the composition of the cold-drawing lubricant may include: sodium phosphate dodecahydrate, sodium fluoride, acetic acid, and water; the mass ratio of sodium phosphate dodecahydrate, sodium fluoride, acetic acid, and water is (48~52) g: (18~22) g: (40~60) mL: 1 L, preferably (49~51) g: (19~21) g: (45~55) mL: 1 L, more preferably 50 g: 20 g: 50 mL: 1 L; the concentration of acetic acid is 36~40 wt%, preferably 36~38%. By limiting the composition and content of the cold-drawing lubricant to the above ranges, the present invention can form a dense cold-drawing layer on the surface of the pipe, reducing the roughness of the inner and outer surfaces of the pipe and improving the fatigue resistance and corrosion resistance of the pipe.
[0075] In one embodiment of the present invention, the number of times the cold-drawing lubricant is applied can be 1 to 4 times, or even 2 to 3 times; the cold-rolled billet can be dried after each application of the cold-drawing lubricant. Limiting the number of applications of the cold-drawing lubricant to the above range ensures the compactness of the cold-drawing die.
[0076] In one embodiment of the present invention, graphite emulsion or molybdenum disulfide lubricant can be coated on the contact surface between the cold-rolled tube blank and the grinding wheel during the multi-pass cold drawing process. The present invention improves cold drawing performance by coating the contact surface between the cold-rolled tube blank and the grinding wheel with lubricant.
[0077] In one embodiment of the present invention, the mandrel selected in the multi-pass cold drawing process is not subject to any special requirements.
[0078] In one embodiment of the present invention, the cross-sectional area reduction rate of each pass in the multi-pass cold drawing can be independently 5-35%, or 10-30%. By limiting the cross-sectional area reduction rate of each pass in the multi-pass cold drawing to the above range, the present invention can ensure that the tube does not break during the cold drawing process and endow the tube with high precision and high surface quality.
[0079] In one embodiment of the present invention, each cold drawing pass in the multi-pass cold drawing process can be followed by online annealing. The temperature of the online annealing process can be independently set to 700-750°C, 710-730°C, or 720°C. The time for the online annealing process after each cold drawing pass can be 1-5 minutes or 2-4 minutes. The present invention limits the temperature and time of the annealing process after each cold drawing pass to the above-mentioned ranges to remove stress, and, in conjunction with the work hardening and grain refinement mechanisms of cold drawing, achieves high strength while imparting high precision and high surface quality to the cold-drawn tube.
[0080] This invention ensures that the titanium alloy matrix has good corrosion resistance by limiting the composition of the titanium alloy; and by melting, forging, hot extrusion and cold rolling the titanium alloy, ultra-long titanium alloy cold-rolled tube blanks can be obtained.
[0081] The present invention also provides a titanium alloy cold-drawn seamless ultra-long tube prepared by the preparation method described in the above technical solution.
[0082] In this invention, the titanium alloy cold-drawn seamless ultra-long tube has a yield strength ≥755MPa, a tensile strength ≥860MPa, an elongation after fracture ≥10%, a tube diameter of Φ3.0~Φ50.8mm, and a single tube length ≥100m.
[0083] In this invention, the titanium alloy cold-drawn seamless ultra-long tube can be used as a hydraulic and fuel pipeline system for aircraft such as Boeing and Airbus, as well as as a downhole control pipe, hydraulic system pressure measuring pipe, pneumatic control pipeline, or environmental control system pressure tapping pipe.
[0084] In an embodiment of the present invention, the fabrication process of the titanium alloy cold-drawn seamless ultra-long tube is shown in the following flowchart. Figure 1 As shown: from Figure 1 As can be seen, after the titanium alloy is smelted (to obtain an ingot through smelting and casting), it is forged. After forging, the oxide scale of the forged billet is removed, and then the billet is hot extruded. The oxide scale of the hot-extruded billet is removed, and then it is skew-rolled and pierced. The oxide scale of the tube blank obtained by skew-rolling and piercing is removed, and then it is cold-rolled and annealed (cold rolling treatment and annealing treatment after each cold rolling) and descaled. Finally, it is cold-drawn and annealed (cold drawing treatment and annealing treatment after each cold drawing) to obtain a cold-drawn seamless ultra-long titanium alloy tube.
[0085] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0086] Example 1 A method for preparing a cold-drawn seamless ultra-long titanium alloy tube (Φ38.1mm×2.0mm, length 500m) comprises the following steps: (1) Smelting: 3.0 tons of finished titanium alloy cold-drawn seamless ultra-long tubes were prepared. Based on the finished product rate of 56% for titanium alloy cold-drawn tubes, 5.3 tons of titanium alloy need to be smelted. The titanium alloy was smelted, cast and first post-processed in a plasma cold-bed large-tonnage smelting furnace to obtain ingots. The first post-processing consisted of flaw detection, first descaling and first flaw detection grinding. The chemical composition of the titanium alloy was: aluminum 3.0%, vanadium 2.5%, iron 0.20%, carbon 0.06%, nitrogen 0.02%, hydrogen 0.12%, oxygen 0.1% and the balance Ti. The ingot was Φ850mm×2050mm. The specific flaw detection method is as follows: In accordance with the testing method of GB / T 5193-2020, low-frequency ultrasonic flaw detection (water immersion ultrasonic method) is used to control the density and purity of the ingot structure, ensuring that the ingot does not contain high-density inclusions (tungsten and molybdenum fragments) and low-density inclusions (oxides and nitrides), and meets the standard of GB / T 5193-2020. The first descaling process involves using a heavy-duty lathe to remove the oxide scale from the surface of the ingot, with a thickness of 4 mm to be removed. The first flaw detection and grinding process involves: manually inspecting the ingot after peeling with heavy machine oil; using a 5MHz small crystal straight probe to check for minor defects in the near-surface area (0~100mm); using a 2.25MHz straight probe to check for minor defects in the middle area (100mm~400mm); and using a 1.0MHz high-power straight probe to check for larger defects in the core (>400mm). The flaw detection defect locations are then ground with a grinding wheel to remove the flaw detection defects. The flaw detection and grinding test results must meet the standards of GB / T 5193-2020. (2) Forging: After obtaining the ingot, the ingot is subjected to forging treatment and a second post-treatment to obtain a forging billet; First firing: β phase region initialization (fragmented as-cast structure), cross-sectional change rate 59.6%. Heating temperature: 1050℃, hold for 30 hours, lightly press and chamfer to eliminate the sharp edges on the surface of the ingot. Since the original length-to-diameter ratio is 2.4, it is not advisable to directly upset it by a large amount (it is easy to become unstable and bend). Use flat anvils or V-shaped anvils to directly elongate it. First, elongate the Φ850mm×2040mm to Φ540mm×5050mm. Perform a large deformation of about 60% at high temperature to completely break the coarse casting dendrite structure and break the grain boundary network structure. Second firing: α+β phase region reforging (grain refinement), cross-sectional change rate 50.5% Heating temperature: 900℃. Using a large reduction in lengthening (lengthening ratio ≥1.5), Φ540mm×5050mm is drawn to approximately Φ380mm×10200mm. Severe deformation occurs in the two-phase region, which promotes the full interweaving of the α and β phases and complete dynamic recrystallization, resulting in a uniform equiaxed fine-grained structure. This is the key to ensuring that subsequent extrusion does not crack. Third firing: Finishing and shaping (standardized dimensions), cross-sectional change rate 15.2%. Heating temperature: 870℃. A small reduction is used for drawing, chamfering and rounding. The forging size of Φ380mm×10200mm is precisely trimmed to the designed Φ350mm×12000mm to ensure cylindricity and straightness, providing a reference for subsequent machining. The second post-processing consists of a second descaling treatment and a second flaw detection and grinding performed sequentially. The second descaling process specifically involves: sequentially sandblasting or alkaline washing, acid washing (HF, HNO3 and water, wherein the volume concentration of HF in the acid solution is 4% and the volume concentration of HNO3 in the acid solution is 30%), water washing (washing with hot water at 50°C), and then mechanical grinding to remove the oxide scale that was not removed after acid washing; The second flaw detection and grinding operation is as follows: manually use heavy machine oil to perform defect detection on the descaling forging billet, use a 5MHz small crystal straight probe to check for small defects in the near-surface area (0~100mm), use a 2.25MHz straight probe to check for small defects in the middle area (100~400mm), grind the flawed locations with a grinding wheel to remove the flaws, and the flaw detection and grinding test results must meet the standard of "GB / T 5193-2020"; (3) After obtaining the forging billet, the Φ350mm×6000mm billet is heated to 900℃ and held for 2.5h. The surface is coated with glass lubricant and a glass pad is used at the die. The billet is then hot-extruded to Φ165mm×54000mm. Intermediate annealing and surface cleaning are then performed. The cross-sectional change rate at this stage is 77.8%, and the extrusion ratio is 4.50. Intermediate annealing and surface cleaning are then performed. The Φ165mm×27000mm billet is cut into 5m lengths. After hot extrusion, the forging billet undergoes a third descaling treatment, drying, and a third flaw detection and grinding process to obtain a hot-extruded tube blank. When heated to the hot extrusion temperature, it is first held in a preheating section at 450℃~500℃ for 1~1.5h (the time can be appropriately shortened as the extrusion cross-section decreases) to eliminate thermal stress, and then raised to the target extrusion temperature. The third descaling process specifically involves immersing the hot-extruded billet in an acid solution (a mixture of HF, HNO3, and water; the volume concentration of HF in the acid solution is 4%; the volume concentration of HNO3 in the acid solution is 30%) for acid washing, followed by water washing to remove the oxide scale; the water used for the water washing is hot water (50°C). The third flaw detection and grinding operation is as follows: According to GB / T 5193-2020, the contact detection method is used to perform ultrasonic flaw detection on the peeled hot-rolled pipe. After flaw detection, the defect location is marked, and the pipe defect is removed by an angle grinder. (4) After obtaining the hot extruded tube blank, the Φ165mm×5000mm hot extruded bar is heated online to 650℃ and held for 1.0h, then heated to 920℃ (below the TA18 phase transformation point) and held for 1.5h for heat penetration; the Φ165mm hot extruded bar is pierced through a skew rolling mill to a Φ175mm×22mm×11.0m rough tube, and then the fourth descaling treatment and the fourth flaw detection and grinding are carried out in sequence to obtain a thick-walled tube; the total cross-sectional change rate during the skew rolling piercing is 57.4%; The fourth descaling process is as follows: the billet obtained by skew rolling and piercing is immersed in an acid solution (a mixed solution of HF, HNO3 and water; the volume concentration of HF in the acid solution is 4%; the volume concentration of HNO3 in the acid solution is 30%) for pickling and then washed with water to remove the oxide scale; the water used for washing is hot water (50°C). The fourth flaw detection and grinding operation is as follows: Ultrasonic and eddy current testing are performed online on the tube blank after the fourth descaling treatment using the ultrasonic flaw detection method of titanium and titanium alloy tubes in GB / T 12969.1 and the eddy current testing method of titanium and titanium alloy tubes in GB / T 12969.2. If the flaw detection results meet the standard requirements, the defect location is ground to eliminate the defect. (4) After obtaining the thick-walled tube, the thick-walled tube is subjected to multiple cold rolling and fifth flaw detection and grinding to obtain a cold-rolled tube blank. The specific process of multi-pass cold rolling is as follows: Rough cold rolling First pass rough rolling: The Φ175mm×22mm×11m tube blank is cold rolled to Φ145mm×18mm×16.2m. The diameter reduction rate of this pass is 17.1%, the wall reduction rate is 18.2%, the Q value (the ratio of diameter reduction rate to wall reduction rate) is 1.06, and the cross-sectional change rate is 32.1%. Second rough rolling pass: After intermediate annealing (holding at 700℃ for 1 hour and furnace cooling), Φ145mm×18mm×16.2m is cold rolled to Φ115mm×14mm×26.2m. The diameter reduction rate of this pass is 20.7%, the wall reduction rate is 22.2%, the Q value is 1.07, and the cross-sectional change rate is 38.2%. Third pass rough rolling: After intermediate annealing (holding at 700℃ for 1 hour and furnace cooling), Φ115mm×14mm×26.2m is cold rolled to Φ90mm×11mm×42.6m. The diameter reduction rate of this pass is 21.7%, the wall reduction rate is 21.4%, the Q value is 0.99, and the cross-sectional change rate is 38.5%. Fourth pass rough rolling: After intermediate annealing (holding at 700℃ for 1 hour and furnace cooling), Φ90mm×11mm×42.6m is cold rolled to Φ72mm×8.5mm×68.6m. The diameter reduction rate of this pass is 20.0%, the wall reduction rate is 22.7%, the Q value is 1.14, and the cross-sectional change rate is 37.9%. Finishing rolling: First pass finishing rolling: The Φ72mm×8.5mm×68.6m tube blank was intermediate annealed (held at 700℃ for 1 hour and then furnace cooled) and then cold rolled to Φ64mm×6.2mm×103.2m. The diameter reduction rate of this pass was 11.1%, the wall reduction rate was 27.1%, the Q value was 2.44, and the cross-sectional change rate was 33.5%. Second pass finishing rolling: After intermediate annealing (holding at 700℃ for 1 hour and furnace cooling), Φ64mm×6.2mm×103.2m is cold rolled to Φ56mm×4.8mm×150.4m. The diameter reduction rate of this pass is 12.5%, the wall reduction rate is 22.6%, the Q value is 1.81, and the cross-sectional change rate is 31.4%. The third finishing rolling pass: After intermediate annealing (heat cooling at 680℃ for 1 hour), the Φ56mm×4.8mm×150.4m tube blank is cold rolled to Φ50mm×3.7mm×215.8m. The diameter reduction rate of this pass is 10.7%, the wall reduction rate is 22.9%, the Q value is 2.14, and the cross-sectional change rate is 30.3%. Fourth pass finishing rolling (finished product pass): After intermediate annealing (heating at 680℃ for 1 hour and furnace cooling), Φ50mm×3.7mm×215.8m is cold rolled to the finished size Φ45.0mm×3.4mm×261.3m. The diameter reduction rate of this pass is 10.0%, the wall reduction rate is 8.1%, the Q value is 0.81, and the cross-sectional change rate is 17.4%. The fifth flaw detection and grinding operation can be specifically as follows: use the ultrasonic flaw detection method for titanium and titanium alloy tubes in GB / T 12969.1 and the eddy current testing method for titanium and titanium alloys in GB / T 12969.2 to perform ultrasonic and eddy current flaw detection on cold-rolled tube blanks online. If the flaw detection results meet the requirements of GB / T 3625, grind the defect location and remove the oxide scale from the defect area. (6) After obtaining the cold-rolled tube blank, the surface of the cold-rolled tube blank is wetted with cold drawing lubricant (the number of times the cold drawing lubricant is wetted is 3 times, and the cold-rolled tube blank is dried after each time it is wetted with cold drawing lubricant) and then cold-drawn in multiple passes to obtain a titanium alloy cold-drawn seamless ultra-long tube. The cold-drawing lubricant comprises: sodium phosphate dodecahydrate, sodium fluoride, acetic acid, and water; the mass ratio of sodium phosphate dodecahydrate, sodium fluoride, acetic acid, and water is 50g:20g:50mL:1L; the concentration of acetic acid is 36%. The specific process of the multi-pass cold drawing is as follows: Process 1: During the cold drawing process, graphite emulsion and molybdenum disulfide lubricant are applied to the contact surface between the cold-rolled tube blank and the mold. The cold-rolled tube blank is induction heated online to 750℃. The outer mold is a tungsten carbide hard alloy mold or a cermet mold, and the inner mold is a fixed cylindrical mandrel. The ultra-long tube with a diameter of Φ45.0mm×3.4mm×261.3m is cold-drawn to Φ40.0mm×2.6mm×380.4m (the cross-sectional area reduction rate is 31.3%), and then annealed online at 720℃ for 3 minutes. Process 2: The outer mold uses a tungsten carbide hard alloy mold or a metal ceramic mold, and the inner mold uses a fixed cylindrical mandrel. The tube is induction heated online to 750℃, and then cold-drawn in a cold drawing mold to cold draw the Φ40.0mm×2.6mm×380.4m ultra-long tube to Φ38.1mm×2.6mm×401.3m (the cross-sectional area reduction rate is 5.2%). It is then annealed online at 720℃ for 3 minutes. Step 3: The tube is induction heated online to 750℃, and then cold-drawn in a cold-drawing mold. The outer mold is a tungsten carbide hard alloy mold or a metal ceramic mold, and the inner mold is a fixed cylindrical mandrel. The ultra-long tube with a diameter of Φ38.1mm×2.6mm×401.3mm is precisely cold-drawn to Φ38.1mm×2.3mm×449.9mm (the cross-sectional area reduction rate is 10.8%), and then annealed online at 720℃ for 3 minutes. Step 4: The tube is induction heated online to 750℃, and then cold-drawn in a cold-drawing mold. The outer mold is a tungsten carbide hard alloy mold or a metal ceramic mold, and the inner mold is a fixed cylindrical mandrel. The ultra-long tube of Φ38.1mm×2.3mm×449.9m is precisely cold-drawn to Φ38.1mm×2.0mm×513.0m (the cross-sectional area reduction rate is 12.3%), and then annealed online at 720℃ for 3 minutes.
[0087] The titanium alloy cold-drawn seamless ultra-long tube prepared in Example 1 was used as a working string in wells with high hydrogen sulfide and carbon dioxide content for a long period of time.
[0088] Example 2 A method for preparing a cold-drawn seamless ultra-long titanium alloy tube (Φ6.4mm×1.2mm, length 900m) comprises the following steps: (1) Smelting: Prepare 175.5 kg of finished titanium alloy cold-drawn seamless ultra-long tubes. Based on the yield of 45-50% of the finished titanium alloy cold-drawn tubes, 50% is taken for smelting, and 351 kg of titanium alloy needs to be smelted. The titanium alloy is smelted, cast and first post-processed by three vacuum self-consuming arc melting (VAR) to obtain ingots. The first post-processing is the sequential flaw detection, first descaling treatment and first flaw detection grinding. The chemical composition of the titanium alloy is: aluminum 3.0%, vanadium 2.5%, iron 0.20%, carbon 0.06%, nitrogen 0.02%, hydrogen 0.12%, oxygen 0.1% and the balance Ti. The ingot is Φ650mm×2400mm. The specific flaw detection method is as follows: In accordance with the testing method of GB / T 5193-2020, low-frequency ultrasonic flaw detection (water immersion ultrasonic method) is used to control the density and purity of the ingot structure, ensuring that the ingot does not contain high-density inclusions (tungsten and molybdenum fragments) and low-density inclusions (oxides and nitrides), and meets the standard of GB / T 5193-2020. The first descaling process involves using a heavy-duty lathe to remove the oxide scale from the surface of the ingot, with a thickness of 3mm to be removed. The first flaw detection and grinding process involves: manually inspecting the ingot after peeling with heavy machine oil; using a 5MHz small crystal straight probe to check for minor defects in the near-surface area (0~100mm); using a 2.25MHz straight probe to check for minor defects in the middle area (100mm~400mm); and using a 1.0MHz high-power straight probe to check for larger defects in the core (>400mm). The flaw detection defect locations are then ground with a grinding wheel to remove the flaw detection defects. The flaw detection and grinding test results must meet the standards of GB / T 5193-2020. (2) Forging: After obtaining the ingot, the ingot is subjected to forging treatment and a second post-treatment to obtain a forging billet; First firing: β phase region initialization (fragmented as-cast structure), cross-sectional change rate 54.1%. Heating temperature: 1050℃, hold for 22h, lightly press and chamfer to eliminate the sharp edges on the surface of the ingot. Due to the large original length-to-diameter ratio (about 3.7), it is not advisable to directly upset it (it is easy to become unstable and bend). Instead, use flat anvils or V-shaped anvils to directly elongate the ingot from Φ650mm×2400mm to about Φ440mm×5.2m. Perform large deformation at high temperature (the allowable deformation degree for billet opening is 50%~70%) to fully break up the coarse casting dendrite structure and break up the grain boundary network structure. Second firing: α+β phase region reforging (grain refinement), cross-sectional change rate 50.2%. Heating temperature: 900℃. A large reduction in length (lengthening ratio ≥ 1.5) is used to draw the Φ440mm×5.2m material to approximately Φ310mm×10.5m. This process causes intense deformation in the two-phase region, promoting the full interweaving of the α and β phases and resulting in complete dynamic recrystallization, thus obtaining a uniform equiaxed fine-grained structure. This is crucial to ensuring that subsequent extrusion does not crack. Third firing: Finishing and shaping (standardized length), cross-sectional change rate 18.4% Heating temperature: 880℃. A small reduction is used for drawing, chamfering, and rounding to trim the Φ310mm×10.5m to the designed Φ280mm×12.9m. During the finishing stage, the deformation is strictly controlled to within 20% to avoid new work hardening and residual stress damaging the equiaxed fine grain structure. Considering the long final length (12.9m), special attention must be paid to using a center rest to prevent bending. The forging dimensions are precisely trimmed to the designed Φ280mm×12.9m to ensure cylindricity and straightness, providing a reference for subsequent machining. The second post-processing consists of a second descaling treatment and a second flaw detection and grinding performed sequentially. The second descaling process specifically involves: sequentially sandblasting or alkaline washing, acid washing (HF, HNO3 and water, wherein the volume concentration of HF in the acid solution is 4% and the volume concentration of HNO3 in the acid solution is 30%), water washing (washing with hot water at 50°C), and then mechanical grinding to remove the oxide scale that was not removed after acid washing; The second flaw detection and grinding operation is as follows: manually use heavy machine oil to perform defect detection on the descaling forging billet, use a 5MHz small crystal straight probe to check for small defects in the near-surface area (0~100mm), use a 2.25MHz straight probe to check for small defects in the middle area (100~400mm), grind the flawed locations with a grinding wheel to remove the flaws, and the flaw detection and grinding test results must meet the standard of "GB / T 5193-2020"; (3) After obtaining the forging billet, the forging billet is subjected to multiple hot extrusions (3 times) and then subjected to the third descaling treatment, drying and third flaw detection and grinding to obtain the hot extruded tube blank; when heating to the hot extrusion temperature, it is first held in the preheating section at 450℃~500℃ for 1~1.5h (the time can be appropriately shortened as the extrusion cross section decreases) to eliminate thermal stress, and then raised to the target extrusion temperature; The Φ280mm×1950mm billet is heated to 870℃ and held for 2.5h. The surface is coated with glass lubricant and fitted with a die glass pad. The extrusion speed is controlled at 60mm / s and extruded to Φ140mm×7.8m. The cross-sectional change rate at this stage is 75.0% (large cross-section open extrusion crushed structure), and the extrusion ratio is 4. The Φ140mm×7.8m billet was heated to 860℃ and held for 2 hours. The surface was coated with glass lubricant and a glass pad was used at the die. The extrusion speed was controlled at 75mm / s. Then, a second hot extrusion was performed. The Φ140mm billet was heated to 870℃ again and coated with glass lubricant. It was then extruded to Φ70mm×31.2m. The cross-sectional change rate at this stage was 75.0% (further refining the grain structure). The extrusion ratio was 4. The extruded bar was then cut to 5m lengths. The third descaling process specifically involves immersing the hot-extruded tube blank in an acid solution (a mixture of HF, HNO3, and water; the volume concentration of HF in the acid solution is 4%; the volume concentration of HNO3 in the acid solution is 30%) for acid pickling, followed by water washing to remove the oxide scale; the water used for the water washing is hot water (50°C). The third flaw detection and grinding operation is as follows: According to GB / T 5193-2020, the contact detection method is used to perform ultrasonic flaw detection on the peeled hot-rolled pipe. After flaw detection, the defect location is marked, and the pipe defect is removed by an angle grinder. (4) After obtaining the hot extruded tube blank, the Φ70mm×5m solid tube blank is continuously heated to 860℃ in an online heating furnace. The surface is coated with glass lubricant and lubricated with the mandrel. The speed of the rolls and the feed angle are controlled to continuously roll and pierce the tube to a rough tube of Φ73mm×8.0mm×11.8m. The cross-sectional change rate at this stage is 57.6% (the solid blank in the α+β two-phase region is pierced and the structure is broken). Then, the fourth descaling treatment and the fourth flaw detection and grinding are carried out in sequence to obtain the thick-walled tube. The fourth descaling process is as follows: the billet obtained by skew rolling and piercing is immersed in an acid solution (a mixed solution of HF, HNO3 and water; the volume concentration of HF in the acid solution is 4%; the volume concentration of HNO3 in the acid solution is 30%) for pickling and then washed with water to remove the oxide scale; the water used for washing is hot water (50°C). The fourth flaw detection and grinding operation is as follows: Ultrasonic and eddy current testing are performed online on the tube blank after the fourth descaling treatment using the ultrasonic flaw detection method of titanium and titanium alloy tubes in GB / T 12969.1 and the eddy current testing method of titanium and titanium alloy tubes in GB / T 12969.2. If the flaw detection results meet the standard requirements, the defect location is ground to eliminate the defect. (4) After obtaining the thick-walled tube, the thick-walled tube is subjected to multiple cold rolling and fifth flaw detection and grinding to obtain a cold-rolled tube blank. The specific process of multi-pass cold rolling is as follows: Rough cold rolling stage The diameter of the material was cold-rolled from Φ73mm×8.0mm×11.8m to Φ54mm×6.5mm×19.9m. The diameter reduction rate was 26.0%, the wall reduction rate was 18.8%, the Q value was 0.72, and the cross-sectional change rate was 40.6%. After intermediate annealing (online annealing at 720℃ for 3 minutes, followed by degreasing and pickling), the Φ54mm×6.5mm×19.9m material was cold-rolled to Φ41mm×5.0mm×34.1m. The diameter reduction rate for this pass was 24.1%, the wall reduction rate was 23.1%, the Q value was 0.96, and the cross-sectional change rate was 41.7%. After intermediate annealing (online annealing at 720℃ for 3 min, followed by degreasing and pickling), the Φ41mm×5.0mm×34.1m material was cold-rolled to Φ31mm×3.8mm×59.4m. The diameter reduction rate for this pass was 24.4%, the wall reduction rate was 24.0%, the Q value was 0.98, and the cross-sectional change rate was 42.6%. After intermediate annealing (online annealing at 720℃ for 3 min, degreasing, and pickling), the Φ31mm×3.8mm×59.4m material was cold-rolled to Φ23.5mm×2.9mm×102.6m. The diameter reduction rate for this pass was 24.2%, the wall reduction rate was 23.7%, the Q value was 0.98, and the cross-sectional change rate was 42.2%. Precision cold rolling stage After intermediate annealing (online annealing at 720℃ for 3 minutes, followed by degreasing and pickling), the Φ23.5mm×2.9mm×102.6m material was cold-rolled to Φ19mm×2.4mm×153.8m. The diameter reduction rate for this pass was 19.1%, the wall reduction rate was 17.2%, the Q value was 0.90, and the cross-sectional change rate was 33.3%. After intermediate annealing (online annealing at 720℃ for 3 minutes, followed by degreasing and pickling), the Φ19mm×2.4mm×153.8m material was cold-rolled to Φ15.5mm×2.1mm×217.5m. The diameter reduction rate for this pass was 18.4%, the wall reduction rate was 12.5%, the Q value was 0.68, and the cross-sectional change rate was 29.3%. After intermediate annealing (online annealing at 720℃ for 3 minutes, followed by degreasing and pickling), the Φ15.5mm×2.1mm×217.5m material was cold-rolled to Φ12.5mm×2.0mm×292.1m. The diameter reduction rate for this pass was 19.4%, the wall reduction rate was 4.8%, the Q value was 0.25, and the cross-sectional change rate was 25.5%. After intermediate annealing (online annealing at 720℃ for 3 minutes, followed by degreasing and pickling), the Φ12.5mm×2.0mm×292.1m material was cold-rolled to Φ10mm×2.0mm×383.3m. The diameter reduction rate for this pass was 20.0%, the wall reduction rate was 0%, the Q value was 0, and the cross-sectional change rate was 23.8%. The fifth flaw detection and grinding operation can be specifically as follows: use the ultrasonic flaw detection method for titanium and titanium alloy tubes in GB / T 12969.1 and the eddy current testing method for titanium and titanium alloys in GB / T 12969.2 to perform ultrasonic and eddy current flaw detection on cold-rolled tube blanks online. If the flaw detection results meet the requirements of GB / T 3625, grind the defect location and remove the oxide scale from the defect area. (6) After obtaining the cold-rolled tube blank, the surface of the cold-rolled tube blank is wetted with cold drawing lubricant (the number of times the cold drawing lubricant is wetted is 3 times, and the cold-rolled tube blank is dried after each time it is wetted with cold drawing lubricant) and then cold-drawn in multiple passes to obtain a titanium alloy cold-drawn seamless ultra-long tube. The cold-drawing lubricant comprises: sodium phosphate dodecahydrate, sodium fluoride, acetic acid, and water; the mass ratio of sodium phosphate dodecahydrate, sodium fluoride, acetic acid, and water is 50g:20g:50mL:1L; the concentration of acetic acid is 36%. The specific process of the multi-pass cold drawing is as follows: Process 1: During the cold drawing process, the contact surface between the cold-rolled tube blank and the mold is coated with graphite emulsion and molybdenum disulfide lubricant. The outer mold is made of TiAlN hard alloy with a surface coating, and the inner mold uses a short moving mandrel to induction heat the cold-rolled tube blank online to 750℃. The Φ10mm×2mm×383.3m tube is cold drawn to Φ8.4mm×2.0mm×479.1m (the cross-sectional area reduction rate is 20%), and then annealed online at 720℃ for 2 minutes. Step 2: The outer mold surface is coated with TiAlN hard alloy, and the inner mold uses a short moving mandrel. The tube is induction heated online to 750℃, and then cold drawn in a cold drawing mold to cold draw the Φ8.4mm×2.0mm×479.1m tube to Φ7.2mm×1.6mm×684.5m (the cross-sectional area reduction rate is 30%). It is then annealed online at 720℃ for 2 minutes. Step 3: The tube is induction heated online to 750℃, and then cold-drawn in a cold drawing mold. The outer mold is made of TiAlN hard alloy with a surface coating, and the inner mold is made of a short moving mandrel. The Φ7.2mm×1.6mm×684.5m tube is cold-drawn to Φ6.4mm×1.2mm×982.8m (the cross-sectional area reduction rate is 30.4%), and then annealed online at 720℃ for 3min.
[0089] The titanium alloy cold-drawn seamless ultra-long tube prepared in Example 2 was used as a downhole control pipe.
[0090] The metallographic structure of the cold-drawn seamless ultra-long titanium alloy tube prepared in Example 1 was observed using a TESCAN MIRA3 XMU scanning electron microscope. The metallographic structure image is shown below. Figure 2 As shown.
[0091] The mechanical properties of the cold-drawn seamless titanium tubes obtained in Examples 1 and 2 were tested using an E45.305 electronic testing machine. In Example 1, the yield strength of the cold-drawn seamless titanium tube was 760 MPa, the tensile strength was 880 MPa, and the elongation after fracture was 13%. In Example 2, the yield strength of the cold-drawn seamless titanium tube was 790 MPa, the tensile strength was 890 MPa, and the elongation after fracture was 10%.
[0092] The preparation method provided by this invention produces cold-drawn seamless titanium tubes with a yield strength ≥755MPa, tensile strength ≥860MPa, elongation after fracture ≥10, and single tube length ≥100m, exhibiting high strength and high corrosion resistance.
[0093] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a cold-drawn seamless ultra-long titanium alloy tube, comprising: Titanium alloy is sequentially smelted, forged, hot extruded, skew rolling pierced, multi-pass cold rolling and multi-pass cold drawing to obtain a seamless ultra-long titanium alloy tube. The titanium alloy, by mass percentage, comprises: aluminum 0~6.0%, vanadium 0~4.5%, tin 0~3.0%, palladium 0~0.25%, iron 0~0.3%, carbon 0~0.08%, hydrogen 0~0.015%, oxygen 0~0.15%, nitrogen 0~0.05%, and the balance Ti; The multi-pass cold rolling includes roughing and finishing; the ratio of diameter reduction to wall reduction in each roughing pass is independently 0.53 to 1.
40.
2. The preparation method according to claim 1, characterized in that, The forging process includes blanking and drawing in the β phase region, reforging in the α+β phase region, and finishing.
3. The preparation method according to claim 2, characterized in that, The cross-sectional change rate of the β-phase region during billet drawing is 50-70%; The cross-sectional change rate of the α+β phase region forging is 40-55%; The cross-sectional change rate of the finishing process is 10-20%.
4. The preparation method according to claim 1, characterized in that, The hot extrusion is a single-pass or multi-pass hot extrusion; the temperature of each hot extrusion in the single-pass or multi-pass hot extrusion is independently 850~1000℃; the cross-sectional change rate of each hot extrusion is independently 66.7~90%; and the extrusion ratio of each hot extrusion is independently 3~10.
5. The preparation method according to claim 1, characterized in that, The cross-sectional area reduction rate for each roughing pass is independently 20-45% to avoid surface microcracks in the alloy under large deformation in a single pass.
6. The preparation method according to claim 5, characterized in that, When the cumulative cross-sectional area reduction rate during the rough rolling stage reaches 50-70%, an intermediate annealing treatment is performed to eliminate work hardening; the intermediate annealing treatment temperature is 700-800℃, the holding time is 1-2h, and then air cooling is performed.
7. The preparation method according to claim 1, characterized in that, The total cross-sectional area reduction rate of the finishing mill is 15-45%; the cross-sectional area reduction rate of each finishing mill pass is independently 10-35%.
8. The preparation method according to claim 1, characterized in that, The cold drawing lubricant used in the multi-pass cold drawing process consists of sodium phosphate dodecahydrate, sodium fluoride, acetic acid, and water.
9. The preparation method according to claim 8, characterized in that, The ratio of the mass of sodium dodecahydrate, the mass of sodium fluoride, the volume of acetic acid, and the volume of water is (48~52) g : (18~22) g : (40~60) mL : 1 L; the concentration of acetic acid is 36~40 wt%.
10. The titanium alloy cold-drawn seamless ultra-long tube prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A titanium alloy coiled tubing and its manufacturing method
CN104404299B
High-strength titanium alloy suitable for cold rolling, preparation method of high-strength titanium alloy, titanium alloy cold-rolled tube and preparation method thereof
CN110983105A
Production and preparation methods of pure titanium or titanium alloy continuous tubing
CN114523271B
A method for preparing high-strength titanium alloy cold-rolled pipe
CN114700387B
Preparation method of TA15 titanium alloy cold-rolled pipe
CN117564728A
